Pencegahan Pekerja Migran Indonesia (PMI) Ilegal - Verawati Skaut; Widodo Triputro (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
The low level of education triggers the development of interest in becoming an illegal PMI because becoming a PMI is the right way and doesn't really cover high levels of education. Kupang Regency itself is the area that contributes the most PMI in NTT, namely 131 people. The condition of the population in Kupang Regency itself whose poverty has increased in the last three years from 88.67 people to 92.02 people with unemployment as many as 94.94 people. Based on this, the authors are interested in researching the prevention of illegal PMI. Based on the type, this research is classified as a qualitative research. The data collection technique used observation, interview and documentation techniques which were then analyzed through the data reduction stage, the data presentation stage and the conclusion drawing. The results of the study show that various efforts to prevent illegal PMI have been carried out by the Kupang Regency Manpower and Transmigration Office, including: Re-checking the required documents to become PMI; Conducting outreach to sub-districts in Kupang Regency; Cooperation with other agencies that are members of the PMI prevention task force; Monitoring BLT and PT Recruitment PMI; Conducting training to improve human resources. In its implementation, the Kupang Regency Manpower and Transmigration Office has tried to take good precautions before, during and after the departure process to become PMI.